(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: This study examined the influence of emotional burnout and digital dependency on pedagogical practices among basic education teachers in public elementary and secondary schools under the Department of Education, Division of Bukidnon, Philippines, for the academic year 2025 - 2026. Employing a quantitative research design, the study gathered data from a representative sample of teachers working in both urban and rural communities. The research utilized descriptive statistics, including mean, frequency distribution, percentage, and standard deviation, to summarize and interpret teachers’ responses regarding their levels of emotional burnout, digital dependency, and pedagogical practices. Correlational and regression analyses were likewise applied to identify the strength of relationships and determine which variable, alone or in combination, best predicted effective teaching practices. Results revealed that teachers experience heightened emotional demands and an increasing reliance on digital tools, both of which greatly influence their instructional strategies and learner interactions. Emotional burnout was found to weaken teacher motivation and engagement, while digital dependency reshaped their planning, communication, and assessment processes. Despite these challenges, teachers displayed resilience by employing adaptive approaches that sustain effective classroom instruction. The findings emphasize the need for continuous professional development, mental health support, and enhanced digital literacy programs that address the evolving demands of technology-driven education. These initiatives are essential for maintaining a supportive teaching environment and ensuring that educators remain equipped to deliver quality and meaningful learning experiences in Philippine basic education.